Natural Convective Heat Transfer from Short Inclined Cylinders - Oosthuizen, Patrick H.; Kalendar, Abdulrahim Y. (SpringerBriefs in Thermal Engineering and Applied Science,, 2014)
Natural Convective Heat Transfer from Short Inclined Cylinders  examines a heat transfer situation of significant, practical importance not adequately dealt with in existing textbooks or in any widely available review papers. Specifically, the book introduces the reader to recent studies of natural convection from short cylinders mounted on a flat insulated base where there is an "exposed" upper surface. The authors considers the effects of the cylinder cross-sectional shape, the cylinder inclination angle, and the length-to-cross sectional size of the cylinder. Both numerical and experimental studies are discussed and correlation equations based on the results of these studies are reviewed. This book is ideal for professionals involved with thermal management and related systems, researchers, and graduate students in the field of natural convective heat transfer, instructors in graduate level courses in convective heat transfer.